Motivation Alignment, Historical Cleavages, and Women's Suffrage in Latin America. Issue 1 (28th March 2023) - Castillo, Isabel
Abstract : Calculations of the electoral effects of incorporating new voters and beliefs on how inclusion alters gender hierarchies constitute two central motivations of decision makers when facing the prospect of suffrage reform. In contrast to the dominant electoral approach, by focusing on the case of early (before World War II) women's suffrage in Latin America, I show that both these motivations are necessary and need to align for reform to occur. To explain the (mis)alignment of electoral calculations and social order concerns in Latin America, I consider the region's historical oligarchic–anti-oligarchic cleavage structure, which is rooted in overlapping class and religious divisions. In most cases, this cleavage produced contradictory motivations and led actors to block women's enfranchisement. Only cases of weak cleavages or low politicization of the issue had early reform. To illustrate the argument, this article uses process tracing to analyze Uruguay and Ecuador as successful early reformers and Peru as a negative case.